Aksesibilitas Sarana dan Prasarana bagi Penyandang Tunadaksa di Universitas Brawijaya - Jefri, Tamba (The Center for Disability Studies and Services Brawijaya University, 2016)
The provision of good accessibility of infrastructure facilities is the main duty of an institution to become an institution that is good for all parties. However, problems frequently arise is still the lack of infrastructure that is less accessible for the disabled. The University of Brawijaya as an institution of higher education higher based inclusive prompted many changes to the accessibility infrastructure that is friendly to people with disabilities, especially physical disabilities (ambulant disabled and. This paper aims to find the accessibility of facilities in the UB for a physical disabled people. With an emphasis on means of pedestrian, doors, lifts, ramps and toilets at some points in UB faculties and buildings.